Here's the quadratic formula:
x=-b±√b^2-4ac/2a
a=1, b=1, c=-1
x=(-1±√(1)^2-4(1*-1)/2(1)
x=(-1±√1+4)/2
x=(-1±√5)/2
2006-12-07 14:24:37
·
answer #1
·
answered by Anonymous
·
4⤊
0⤋
i'd say, use your handy dandy TI-89 or, settle for the good old fashioned quadratic formula which states:
if ax^2 + bx + c = 0, then
x = [ -b +/- sqrt(b^2 - 4ac) ] / 2a
In your equation, a=1, b=1, and c= -1.
Thus: x = [ -1 +/- sqrt (1^2 - 4(1)(-1) ) ] / 2(1)
Simplifying:
x = [ sqrt(5) - 1 ] / 2 AND [ -sqrt(5) - 1] / 2
2006-12-07 14:10:26
·
answer #2
·
answered by InsaneOrCroak 2
·
2⤊
0⤋
In equation: a x^2 + bx + c = 0 then:
x =( -b +/- sqrt (b^2 - 4ac) ) / 2a
x = -1 +/- sqrt (1+4) / 2
x = ( -1 - sqrt (5)) / 2 and ( -1 + sqrt (5)) / 2
2006-12-07 14:11:38
·
answer #3
·
answered by Anonymous
·
1⤊
0⤋
x^2+x-1=0
Use the formula where a=1, b=1, c=-1
x=0.618 or x=-1.618
I checked them using the calculator! ;)
2006-12-07 14:10:32
·
answer #4
·
answered by Max D 3
·
1⤊
0⤋
x = -.5 ± (√5)/2
In decimal form this is .618..... and 1.618...., the ratio of the sides of the 'golden rectangle' known to the ancient Greeks and incorporated into much of their architecture.
2006-12-07 14:14:23
·
answer #5
·
answered by Steve 7
·
1⤊
0⤋
ax^2+bx+c=0
x= ( -b +/- sqrt(b^2-4ac) ) / (2a)
in your case, a=1, b=1, c=-1.
2006-12-07 14:07:41
·
answer #6
·
answered by Anonymous
·
1⤊
0⤋
use quadratic formula...or factor it out, use your graphing calculator
(if you have one)
2006-12-07 14:37:47
·
answer #7
·
answered by Anonymous
·
1⤊
0⤋
its not solvable or the answer is in fractions decimals...
2006-12-07 14:09:09
·
answer #8
·
answered by Anonymous
·
0⤊
1⤋
x=[-1+/-sq.rt(1+4)]/2
=[-1+/-sq.rt5]/2
x1=(-1+rt5)/2
x2=(-1-rt5)/2
2006-12-07 14:08:40
·
answer #9
·
answered by raj 7
·
1⤊
0⤋
DO. YOUR. OWN. HOMEWORK.
2006-12-07 14:07:26
·
answer #10
·
answered by kittenpie 3
·
1⤊
2⤋